Inhibitory effect of verapamil on Candida albicans hyphal development, adhesion and gastrointestinal colonization. Issue 4 (3rd April 2014) - Yu, Qilin; Ding, Xiaohui; Zhang, Bing; Xu, Ning; Jia, Chang; Mao, Jiwei; Zhang, Biao; Xing, Laijun; Li, Mingchun
Abstract Candida albicans morphogenesis and gastrointestinal colonization are closely associated with the pathogenicity of this pathogen. This study investigated the in vitro and in vivo effect of verapamil, a calcium channel blocker, on these processes. Exposure to ≥ 10 μg mL−1 verapamil led to a significant decrease of C. albicans hyphal cells. The ability to adhere to a polystyrene surface and buccal epithelial cells was inhibited by exposure to ≥ 20 μg mL−1 verapamil. Detection of the Hwp1–green fluorescent protein fusion protein showed that verapamil inhibited expression and transport of Hwp1, indicating its activity against both the regulation network of morphogenesis‐associated proteins and the secretory pathway in C. albicans. Moreover, treatment with verapamil at 10 mg (kg day)−1 led to a remarkable decrease in gastrointestinal‐colonizing fungal cells. This study revealed the inhibitory effect of verapamil on C. albicans hyphal development, adhesion and gastrointestinal colonization, which is relevant to decreased expression and abnormal transport of the proteins required for morphogenesis. Therefore, verapamil may be taken into account when choosing an antifungal therapy against C. albicans colonization and infection.